THE IMPACT OF CUSTOMER RELATIONSHIP MANAGEMENT TO CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION IN CABAL DINING MANADO - Wattilete, Randy; Pangemanan, Sifrid S.; Pandowo, Merinda (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Customer relationship management is the one influencing customer loyalty, but to get customer loyalty we should know how to make customer satisfaction. This research is purposed to analyze the impact of customer relationship management to customer loyalty through customer satisfaction in Cabal Dining Manado. This research used the Path analysis as the method of this research. Population in this research is mainly in this research is people in Manado. The sample of this research is 100 respondents of random sampling. The interpretation shows that every variable have strong relationship and are supported by significance level. Customers Relationship Management has a significant relationship with customer satisfaction so does customer satisfaction has a significant relationship with customer loyalty. Based on the result done, variable customer relationship management has a significant value to the customer satisfaction variable. Which means Cabal Dining should really pay more attention about how they built a relationship with their customers. Customer satisfaction is important in determine customer loyalty. By feeling satisfy there is a possibility that people would come again to the places that give them the experience they looking for. Keywords: customer relationship management, customer loyalty, customer satisfaction